FLUID ORIGIN AND DYNAMIC AT THE NEWLY DEVELOPED THEISTAREYKIR GEOTHERMAL FIELD, ICELAND - Marion Saby; Daniele Pinti; Vincent van Hinsbger; Bjarni Gautason; Ásgerður Sigurðardóttir; Clara Castro; Chris Hall; Jean-François Hélie; Océane Rocher (Zenodo, 2019)
This study aim at deciphering the origin of the fluids and the hydrodynamic of the Theistareykir geothermal system using water isotopes and noble gases as a tracer of these respective contributions. Results first confirm that the magma beneath Theistareykir is a mix between a mantle plume (OIB) and an ocean ridge basalt (MORB). They also show that both magmatic fluids and surface water are present in the system in proportions that are being quantifyed. Water isotopes show that sources of surface water range from modern to Pre-Holocene. A crustal input is also present in the system with an enrichment in δ 18 O highlighting water-rock interaction.